(????? ?????? ????? ??????? ?????? ????? ?????? (????? ??????? THE APPLICATION OF ARABIC GROUP TO IMPROVE SPEAKING SKILL (AN EXPERIMENTAL STUDY) - Ali Mukti (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: The main issue in this research, it is how to apply the Arabic Club to improve the skill of speaking. The purposes of the research are to know how the Arabic language group is, to know the linguistic activity used in the Arabic club, and to know its effect on improving the skill of speaking. The research method, it is field research on the descriptive approach. In his writing, the researcher used a descriptive and analytical method, then collected data through observation and personal interview with the Arabic language teacher in the Arabic language group program and some students, and then made tests. As for the results of the research, they are the linguistic activity in this program. It consists of three types: conversation or dialogue, simulation and expressions. Among the highlights of the linguistic activity in this program are conversational activities and expressions. In its application it consists of what is related to vocabulary pronunciation, grammatical structures and expression of ideas. As for the highlight of the linguistic activity to upgrade students' speech skills, it is the pronunciation of vocabulary. The Arabic Language Group has the effect of improving the speech skills of students in this program. Speak Arabic with the teacher at 2 Padding High School and their friends when applying this program. One of the advantages of the program is that the pupils find ample opportunity to speak Arabic and practice speaking. As for her problem, it is the lack of time, the lack of interest of the teacher, and the lack of students' attendance for this program. ??????? ????????: ?????? ????? ???????? ?????? ????? ??????